Pengaruh Harga, Promosi Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Paket Wisata Pada Kotoba Tour And Travel Blitar - Budi Setio Zadi; Nur Hidayati; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2020)
AbstractThe purpose of this research is to know the influence of price, promotion, and quality of service to purchase decisions on Kotoba Tour and Travel Blitar. While purchasing decisions as variables are bound. Research population as much as 120 consumers. The sampling in this study was purposive sampling with a total sample of 55 respondents. Quantitative research method with multiple linear regression analysis techniques. Based on the results of this study can be concluded as follows: (a) The price, promotion and quality of service are simultaneously influence on the decision of purchasing tour packages in Kotoba Tour and Travel Blitar. (b) Price affects the decision to purchase tour packages in Kotoba Tour and Travel Blitar. (c) Promotion of the decision to purchase tour packages on Kotoba Tour and Travel Blitar. (d) The quality of service affects the decision to purchase tour packages in Kotoba Tour and Travel Blitar.Keywords: price, promotion, service quality, purchase decision